Forming taxon names from Greek words - Vlachos, Evangelos (2015)
Ever since the times of Linnaeus, the use of Latinized Greek names for naming the present and past diversity of our planet has been a common practice. This contribution focuses on the use of Greek words in forming taxon names, as exemplified by names from chelonian literature. The current problems of the guidelines of the International Code of Zoological Nomenclature about the successful transliteration and Latinization of Greek words are illustrated through various examples, and several improvements and changes in the system currently recommended by the Code are proposed.